Electrodeposition of coercive ferromagnetic films - Filho, Fernando Mário Rhen (Trinity College (Dublin, Ireland). School of Physics, 2005)
The need for even more compact and low power consumption devices has been the driving force for microeiectromechanical systems (MEMS). Also the integration of MEMS into current state of the art silicon technology has set the boundaries for the preparation of these devices. Any candidate device to be manufactured using silicon technology should be integrated at the last step o f production to minimize the cost. To achieve, the maximum annealing temperature should not exceed about 300°C. Many integrated circuits (CMOS) deteriorate above this temperature.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin